Utopia and History of a Mediterranean Atoll, Ideogram of Messina and Calabrian Territory. - Nicola Aricò (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
Two different representations of a medieval icon dating back to the early 16th century or to the late15th century – a senatorial seal and a miniature on a membranous base –, perhaps from the 14th century -  are attributable to the Byzantine workshop of the monastery of the Holy Salvatore of Messina.